Analisis Pengaruh Waktu Fermentasi terhadap Konsentrasi Etanol pada Kulit Pisang Raja (Musa acuminata) dan Pisang Kepok (Musa paradisiaca L) - Rahmadian Hoirunnisa; Khoirul Rista Abidin; Fath Dwisari; Abdurraafi' Maududi Dermawan (Bahiraliya Natura Science, 2025)
Banana peel waste is frequently discarded without proper management, potentially causing long-term environmental problems. However, banana peels can be valorized as a renewable feedstock for ethanol production. This study employed a quantitative experimental design consisting of four main stages: sample preparation, sulfuric acid hydrolysis, yeast fermentation with fermentation time variations of 72, 120, and 168 h, and ethanol content analysis. The ethanol content obtained from Raja banana (Musa acuminata) peels at fermentation times of 72, 120, and 168 h was 15%, 16%, and 17%, respectively. Meanwhile, ethanol yields from Kepok banana (Musa paradisiaca L.) peels at the same fermentation durations were 17.66%, 20.33%, and 22.33%, respectively. The results indicated that the highest ethanol content for both Raja and Kepok banana peels was achieved at a fermentation time of 168 h. Friedman test analysis revealed significance values of 0.368 (> 0.05) for Raja banana peels and 0.097 (> 0.05) for Kepok banana peels, indicating no statistically significant differences in ethanol content among the three fermentation durations. Overall, an increasing trend in ethanol content was observed for both banana varieties with prolonged fermentation time; however, statistical analysis confirmed that the differences were not significant across the tested fermentation periods.